Dilema Etik Dalam Assisted Reproductive Technology (ART) - Nurma Zela Gustina; La Ode Abdul Rahman (Jurnal Keperawatan, 2020)
The development of ART in the community that is important to do is related to ethics and dilemmas that may arise in the use of ART. The Improvement of ART user as solution in Infertility but also not able on rule of ART. This study to provide an overview as well as an overview of the results of a literature review related to ethical dilemmas in actions assisted by reproductive technology. In this study using the literature review method. In ART actions related to problems that become related to embryonic donations that allow recipients of embryonic donors to get disease transmission to later generations. The application of ethics by nurses in ART is able to consider badly the event by exposing embryonic donors and recipients to establish communication in the future. The importance of applying ethics as a better way of preventing diseases arising after ART actions both for donors and donor recipients.